Land Issues in Forest Areas of Yogyakarta Special Region and The Dynamic of Decision Making Process - Soraya Isfandiari; Ambar Widaningrum; Nunuk Dwi Retnandari (Indonesian Association for Public Administration, 2020)
There is a forest land identified as Ab Gronden, located in Gunung Kidul Regency, Yogyakarta Special Region. Ab Gronden occupation has led to prolonged conflict over land until today. Environment and Forestry Service (EFS) of Yogyakarta Special Region has made a decision of “do nothing” from the policy set by central government to solve the problem. This study intends to examine factors underlying the decision of “do nothing